2017
DOI: 10.1007/s00381-017-3691-8
|View full text |Cite
|
Sign up to set email alerts
|

Medical and socioeconomic predictors of quality of life in myelomeningocele patients with shunted hydrocephalus

Abstract: Myelomeningocele patients with shunted hydrocephalus can have a poor health-related quality of life. Our results indicate a strong association of income and family functioning on quality of life, along with younger age and lower level of myelomeningocele.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
1
8
1
Order By: Relevance
“…Studies have confirmed the association between the severity of the condition and QoL. In our analysis, the percentage of patients with hydrocephalus was 43%, which is well below the usual range of 70-86% [30]. The explanation for this is that other studies included all spinal dysraphisms, while our sample only focused on myelomeningocele.…”
Section: Discussioncontrasting
confidence: 41%
“…Studies have confirmed the association between the severity of the condition and QoL. In our analysis, the percentage of patients with hydrocephalus was 43%, which is well below the usual range of 70-86% [30]. The explanation for this is that other studies included all spinal dysraphisms, while our sample only focused on myelomeningocele.…”
Section: Discussioncontrasting
confidence: 41%
“…The HOQ has been used in a number of studies that have examined health outcomes in children with hydrocephalus. 8,[23][24][25] Scoring of the HOQ provides scores from 0.0 (worse health status) to 1.0 (better health status). 26 Internal consistency from the initial test development, measured with Cronbach α, was 0.94 for overall health, 0.93 for physical health, 0.82 for socialemotional health, and 0.91 for cognitive health.…”
Section: Methodsmentioning
confidence: 99%
“…Tilford et al [56] reported that lesion location in childhood SB had a significant impact on overall utility (p < 0.01); individuals with sacral lesions had the highest overall mean utility (0.61; ±0.26). Two studies reported correlation between clinical factors and utility scores in SB [21,38]. Anatomical myelomeningocele level was found to have a significant effect on the HUI utility scores of children with myelomeningocele and shunted hydrocephalus (mean HUI score = 0.03; 95% CI 0.01 to 0.05; p = 0.01) [38], with lower myelomeningocele level showing association with higher utility scores.…”
Section: Spina Bifida Known-group Analysesmentioning
confidence: 98%
“…Two studies reported correlation between clinical factors and utility scores in SB [21,38]. Anatomical myelomeningocele level was found to have a significant effect on the HUI utility scores of children with myelomeningocele and shunted hydrocephalus (mean HUI score = 0.03; 95% CI 0.01 to 0.05; p = 0.01) [38], with lower myelomeningocele level showing association with higher utility scores. A similar trend was reported by Young et al [21], who found that the most important single factor contributing to utility outcomes in SB was surgical lesion level, which was responsible for between 18% (AQoL) and 40% (HUI3) of variance in utility scores.…”
Section: Spina Bifida Known-group Analysesmentioning
confidence: 98%
See 1 more Smart Citation